The dynamics of the health of schoolchildren in Ukraine according to the questionnaire survey - S.L. Nyankovskyy; M.S. Yatsula; O.S. Nyankovska; A.V. Tytusa (Zaslavsky O.Yu., 2018)
Background. For the last decades, the state of health and physical development of the children's population of Ukraine are deteriorating. Among the factors that determine the decline in children's health, educational load plays almost a crucial role, its stressful action leads to a maladjustment syndrome with neurotic reactions of varying severity. Materials and methods. Based on the survey data of schoolchildren of Lviv in 2002 (20,000 pupils), 2013 (32,000) and 2017 (70,000), a comparative analysis was performed on the age-dependent incidence of major complaints and symptoms, medical and social characteristics among 1-11-graders. Results. The state of health of schoolchildren in recent years has no tendency to improve. The most frequent complaints of schoolchildren are abdominal pain, heartburn, nausea, headache, appetite loss, symptoms of vegetative lability and asthenic syndrome, other symptoms of syndrome of school maladjustment, which is probably due to high class load, inadequate nutrition, the effect of stress factors against the background of a significant decline in physical activity. The modern diet of schoolchildren is unbalanced, does not ensure the daily intake of all necessary nutrients, including vitamins and trace elements. Conclusions. A comprehensive approach to assessing the health of schoolchildren, based on objective information, the introduction of new health-improving technologies, the unification of efforts of health workers, teachers and parents can prevent functional disorders and organic pathology in schoolchildren, their chronicity, reduce the symptoms of school maladjustment, increase the level of health in children and their ability to learn, and also prevent the development of diseases in adulthood. At the same time, this technology does not require significant financial investments.